Effect of a school-linked life skills intervention on adolescents' sexual and reproductive health skills in Guji zone, Ethiopia (CRT)—A generalized linear model - Godana, Gobena; Garoma, Silesh; Ayers, Nicola; Abera, Muluembet (Frontiers in Public Health, 2023)
Background: Even though appropriate life skills are a recognized primary adolescent right and a critical component of health policy, it is not well addressed and rarely researched in pastoral communities. Life skills are the ability to adopt positive behavior, which enables individuals to deal effectively with the demands & challenges of everyday life. The study has aimed to evaluate the effectiveness of the School-Linked life skills intervention program on SRH life skills in the pastoral community of Guji Zone. Methods: A two-arm cluster randomized Control trial study with pre-posttests had piloted among intervention (n=375) compared with control (n=384) to assess the effect of school-linked life skills intervention with the usual RH Curriculum as a control arm. Pre-post and post-posttests among the control group and trial groups had compared. The data had collected by 27 Self-administered questions. The data was analyzed using paired-sample independent t-tests & a generalized linear model to examine the relationship between the dependent and independent variables. Results: Data were collected from 759 adolescents who belong to 15 intervention and 15 control clusters. The findings have shown that as compared to controls, the proportion of mean life skills score was identified to be significantly higher in the intervention clusters (375) 70.49% vs. (384) 62.25%, p<0.001 95% CI, (0.06, and 0.1). Adolescents who were trained on school-linked life skills (β: 1.915, 95% CI: 1.411–2.418), confident to make safe & informed decisions (β: 1.999, 95%CI: 1.562–2.436), and life skills to deal with SRH issues (β: 1.66, 95% CI: 1.233–2.087) significantly correlated with life skills prediction. The proportion of adolescents with life skills increased from 150(39.1%) baseline to 252(67.2%) end line in the intervention versus 384(60.31% to 384(62.31%) in control arms, respectively. Conclusions: The implantation of a school-Linked life skills intervention program has proved to have a significant effect on SRH life skills development. Individual-level and behavioral-level variables were important in explaining variability in the life skills development in the pastoral community. We recommended that the intervention be scaled up to all high schools. Trial registration: Trial registration PACTR202107905622610, registered on 16 July 2021. Keywords: Adolescent, life skills, SRH, Pastoral Community